Literature Review: Determinants of Burnout Among Healthcare Workers - Suharto, Muhammad Andi Suharto; Maria Mardate Loma; Mohamad Ariandhy Mokambo; Wira Suana Priyatin; Andri Priantono; Umi Setyoningrum (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Burnout among healthcare workers is an occupational health problem that significantly affects service quality and patient safety. It is characterized by emotional exhaustion, reduced motivation, and decreased performance due to prolonged work-related stress. This study aims to analyze the factors associated with burnout among healthcare workers based on a literature review. The method used was a descriptive literature review of five scientific articles published in 2024–2025 with a cross-sectional quantitative design. Articles were retrieved from Google Scholar, PubMed, and GARUDA databases and analyzed using a comparative descriptive approach. The results indicate that workload, work stress, and job conflict are the main factors associated with increased burnout among healthcare workers. In addition, psychosocial factors such as social support and organizational factors such as work environment and work-life balance also play important protective roles. Meanwhile, demographic factors such as age and length of service show inconsistent results across studies. In conclusion, burnout among healthcare workers is influenced by multidimensional factors, particularly workload and social support, highlighting the need for organizational interventions and psychosocial support to prevent burnout.